The role of IMF conditionality for central bank independence - Andreas Kern; Bernhard Reinsberg; Matthias Rau-Goehring (European Central Bank (ECB), 2020)
This paper studies the role of the International Monetary Fund (IMF) in promoting central bank independence (CBI). While anecdotal evidence suggests that the IMF has been playing a vital role for CBI, the underlying mechanisms of this influence are not well understood. We argue that the IMF has ulterior motives when pressing countries for increased CBI. First, IMF loans are primarily transferred to local monetary authorities. Thus, enhancing CBI aims to insulate central banks from political interference to shield loan disbursements from government abuse. Second, several loan conditionality clauses imply a substantial transfer of political leverage over economic policy making to monetary authorities. As a result, the IMF through pushing for CBI seeks to establish a politically insulated veto player to promote its economic policy reform agenda. We argue that the IMF achieves these aims through targeted lending conditions. We hypothesize that the inclusion of these loan conditions leads to greater CBI. To test our hypothesis, we compile a unique dataset that includes detailed information on CBI reforms and IMF conditionality for up to 124 countries between 1980 and 2014. Our findings indicate that targeted loan conditionality plays a critical role in promoting CBI. These results are robust towards varying modeling assumptions and withstand a battery of robustness checks.
Keywords: E52; E58; F5; 330; Central bank independence; International Monetary Fund; conditionality; international political economy